PERBEDAAN EFEKTIVITAS BERKUMUR REBUSAN DAUN SALAM (SYZYGIUM POLYANTHUM) DENGAN DAUN JAMBU BIJI (PSIDIUM GUAJAVA LIN) TERHADAP PLAK SKOR PADA SISWA KELAS IV, V, DAN VI SDN SUNGAI BATANG 2, KECAMATAN MARTAPURA BARAT, KABUPATEN BANJAR - Lathifah, Khusnul; Kisworo Utami, Naning; Danan, Danan; Sari, Emilda (Poltekkes Kemenkes Banjarmasin, 2025)
structures are in a healthy state. Salam leaf and guava leaf contain substances that inhibit the growth of microorganisms thus preventing plaque growth. This study aims to determine the differences in the effectiveness of gargling with boiled salam leaf (Syzygium polyanthum) with guava leaf (Psidium guajava Lin) on plaque scores in grade IV, V, and VI students of SDN Sungai Batang 2, Martapura Barat District, Banjar Regency. This research design uses a quasi-experimental. The research sampling technique used Total Sampling. The research population was 50 people. The results showed that the plaque score before gargling with boiled salam leaf was 3.656 and after gargling with boiled salam leaf was 1.540, while the plaque score before gargling with boiled guava leaf was 3.752 and after gargling with boiled guava leaf was 1.540.p = 0.000 is smaller than α = 0.05 then H0 rejected and Ha accepted shows there is a difference. Conclusion based on test results Independent T-Test there is a difference in the effectiveness of gargling with boiled bay leaves (Syzygium polyanthum) with guava leaves (Psidium guajava Lin) on plaque scores in grade IV, V, and VI students of SDN Sungai Batang 2, Martapura Barat District, Banjar Regency. It is recommended to use guava leaf decoction as a natural mouthwash that can inhibit plaque in the mouth.